Educação ambiental e corporal: algumas reflexões - Dileno Dustan Lucas de Souza; Laura Pronsato (EccoS – Revista Científica)
The ambient education has been restricted to the speeches of the “green” or the sustainable one. On the other hand, the body is dealt like some specie ofmachine to be disciplined almost in state of confinement and silenciament. This perception leaded us to develope a research with interphase in the extension in a public school of basic education in the city of Viçosa (MG) in intention to understand,on the inside of a school system, how isthe ambient education been treated and with that,to extend the capacity of reflection and awareness on the way that if lives and as the body reacts. The intention of this text is to socialize this experience from pedagogical practices around the ambient and corporal education. Metodologic we work with participant research in the educative environment inside and outside of the school. The activities of corporal and ambient conscience had been related with the corporal awareness , experimentations and reflections.